2006
DOI: 10.1182/blood-2005-07-2676
|View full text |Cite
|
Sign up to set email alerts
|

PKCϵ controls protection against TRAIL in erythroid progenitors

Abstract: Apoptosis plays a central role in the regulation of the size of the hematopoietic stem cell pool as well as in the processes of cell differentiation along the various hematopoietic lineages. TRAIL is a member of the TNF family of cytokines with a known apoptogenic role against a variety of malignant cells and an emerging role in the modulation of normal hematopoiesis. Here we worked on the hypothesis that PKC⑀ could act as a switch of the cellular response to TRAIL during erythropoiesis.We demonstrate that EPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 30 publications
6
71
0
Order By: Relevance
“…18,19,21,22,38 We also found that overexpression of PKCe did not alter the levels of TRAIL receptors or interfere with the recruitment of caspase-8 to the DISC. Overexpression of PKCe caused a decrease in Bid protein and mRNA in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…18,19,21,22,38 We also found that overexpression of PKCe did not alter the levels of TRAIL receptors or interfere with the recruitment of caspase-8 to the DISC. Overexpression of PKCe caused a decrease in Bid protein and mRNA in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that EPOdriven upregulation of PKCe level renders differentiating erythroid cells resistant to TRAIL likely via Bcl-2 upregulation. 21 We have shown that overexpression of PKCe increased Bcl-2 not only at the protein level but also at the mRNA level. In addition, knockdown of PKCe by siRNA decreased Bcl-2 level.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In MCF-7 cells, however, overexpression of the PKCε regulatory domain decreased Bcl-2 protein levels and increased susceptibility to apoptosis induced by multiple factors although the effects of PKCα regulatory domain was more pronounced [133]. It has been reported that EPO-driven upregulation of PKCε levels renders differentiating erythroid cells resistant to TRAIL, likely via Bcl-2 upregulation [134].…”
Section: Pkcε and Bcl-2 Family: Many Partners In The Dance Of Deathmentioning
confidence: 97%